Length-weight relationship of Neolissochilus hexagonolepis (McClelland) and Garra lissorhynchus (McClelland) - Kar, Devashish; Laskar, Boni Amin; Nath, Debasish; Barbhuiya, M H (Indian Journal of Fisheries, 2011)
The length-weight relationship of Neolissochilus hexagonolepis (McClelland) and Garra lissorhynchus (McClelland), collected from Jatinga river in Assam, have been studied. Based on 50 specimens of N.hexagonolepis (70-270 mm) and 72 specimens of G.lissorhynchus (47-94mm), the regression equation was calculated to be Log W=-2.882 + 1.922 Log L and Log W=-5.171 + 3.152 Log L respectively for the two species of fishes. The computed ‘t’ values indicated that ‘n’ value of N.hexagonolepis is significantly different from the expected value of ‘3’. The relative condition factor (Kn) remained greater than 1 for N.hexagonolepis and G.lissorhynchus indicating their good well being.